Corticosteroids in lung cancer - Ćeriman Krstić, Vesna; Gajić, Milija; Djukanović, Leonida; Jovanović, Dragana (Frontiers in Drug Safety and Regulation, 2025)
Despite significant advances in lung cancer treatment, patients with this disease still present with multiple symptoms that are very hard to control. Corticosteroids are widely used in patients with lung cancer, but without clear evidence for their efficacy. Thus, corticosteroids have been used for the treatment of conditions arising due to the tumor itself, adverse effects of the applied specific therapy and symptom palliation. In this review we are going to summarize clinical indications for corticosteroid use in patients with lung cancer: malignant airway obstruction, superior vena cava syndrome, brain metastases, treatment-related adverse events, anorexia and cachexia, fatigue, dyspnea, nausea and vomiting, spinal cord compression, and pain.